2016
DOI: 10.1111/ped.12865
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia in children: Current status and future directions

Abstract: Acute myeloid leukemia (AML) accounts for 25% of pediatric leukemia and affects approximately 180 patients annually in Japan. The treatment outcome for pediatric AML has improved through advances in chemotherapy, hematopoietic stem cell transplantation (HSCT), supportive care, and optimal risk stratification. Currently, clinical pediatric AML studies are conducted separately according to the AML subtypes: de novo AML, acute promyelocytic leukemia (APL), and myeloid leukemia with Down syndrome (ML-DS). Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 88 publications
3
82
1
5
Order By: Relevance
“…Pediatric AML accounts for 15–20% of pediatric leukemia, with survival rates of approximately 70% [66]. In adults, AML is the most common type of leukemia, but only 10–20% of patients older than 60 will be cured [67, 68].…”
Section: Acute Myeloid Leukemia (Aml)mentioning
confidence: 99%
“…Pediatric AML accounts for 15–20% of pediatric leukemia, with survival rates of approximately 70% [66]. In adults, AML is the most common type of leukemia, but only 10–20% of patients older than 60 will be cured [67, 68].…”
Section: Acute Myeloid Leukemia (Aml)mentioning
confidence: 99%
“…Despite the recent advances achieved in the treatment of leukemia in children, the prognosis of relapsed and refractory disease remains dismal with more than 50% mortality rate 13. Acute and long-term toxicities of current chemotherapy agents often limit their further intensification, thus highlighting an urgent need for novel therapeutic approaches to develop newer, safer treatment protocols.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that AML in children accounts for 25% of pediatric leukemia cases and affects ~180 patients annually in Japan (1). A total of 19,000 cases of AML are diagnosed each year, with ~10,000 of these in the United States (2).…”
Section: Introductionmentioning
confidence: 99%